MENELAAH KEMISKINAN DI INDONESIA PERSPEKTIF EKONOMI POLITIK - Oktavianti, Henny (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2008)
The poverty alleviation has been a main problem in Indonesia for a long time. Thenumbers of poverty has been increased for more than onethird in the crisis that hasreturned into the beforecrisis period. Meanwhile, Indonesia has experienced a greattransformation in social and political in line with the development of full spirit ofdemocracy by the existence of government’s decentralization, and also a widertransparency than what we have in the past. The commitment of the government inalleviating poverty has been stated in Rencana Pembangunan Jangka Menengah(RPJM) 20052009 which based on the Strategi Nasional PenanggulanganKemiskinan (SNPK). However, the rate of poverty is still high, viewed from anyfactors. This paper focuses on the discussion of poverty that did not abate in spite ofvarious poverty alleviation programs has been announced by the government. Thewriter has analyzed the absolute phenomena of poverty based on the political view,which the variables are related to the economic growth since the basic economicactivities could affect the level of poverty (Weede, 1986, saunders, 1986, Castles,1990, 1991, in Lane & Ersson, 2002).Keywords: poverty, Indonesia, economic and political perspectives